A fly ash-based defluorination adsorbent material and preparation method thereof

Through the synergistic effect of fly ash, hydroxyapatite modifier and regulation liquid, the problem of low efficiency of fly ash-based fluorine removal materials in the prior art is solved, and efficient and rapid fluorine ion removal effect is achieved.

CN118949940BActive Publication Date: 2024-12-13呼和浩特市生态环境监控中心
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411442937.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2024-12-13
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

Existing fly ash-based fluorine removal materials have low efficiency in removing fluorine ions and slow fluorine removal rate, making it difficult to efficiently and quickly remove fluorine.

Method used

Using the combination of fly ash, hydroxyapatite modifier and regulation solution, the hydroxyapatite activity is optimized through proton irradiation, and the silane coupling agent, lanthanum chloride, chitosan and tablets in the modified solution are used. Graphene agent is combined with blended ball milling of alumina and sodium alginate to prepare an efficient fly ash-based fluorine-depleting adsorbent.

Benefits of technology

The fluorine ion removal efficiency and fluorine removal rate are significantly improved, and efficient and rapid fluorine ion removal is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of adsorbent materials, and in particular to a fly ash-based defluorination adsorbent material and a preparation method thereof, wherein the adsorbent material comprises fly ash, a hydroxyapatite modifier and a conditioning liquid, wherein the mass ratio of the fly ash, the hydroxyapatite modifier and the conditioning liquid is (4-6):(2-4):9. The fly ash-based defluorination adsorbent prepared by the present invention has excellent fluoride ion removal efficiency through the synergistic effect between the raw materials, and has a high defluorination rate, and can remove fluorine efficiently and quickly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorbent materials, and in particular to a fly ash-based defluorination adsorbent material and a preparation method thereof. Background Art

[0002] With the intensification of industrial production, the phenomenon of high-concentration fluorine-containing industrial wastewater discharge is also increasing. Coal mine water, coal chemical industry, photovoltaic, fluorine chemical industry, metal smelting, electroplating and other industries all produce fluorine-containing wastewater and need to undergo corresponding deep treatment before discharge or reuse. The concentration of fluoride (measured in fluoride ions) in the wastewater discharged by these fluorine-containing enterprises into municipal sewage treatment plants is generally around 10 mg / L.

[0003] The fly ash-based defluorination materials prepared in the prior art have poor fluoride ion removal efficiency and a slow defluorination rate, making it difficult to remove fluoride efficiently and quickly, which limits the defluorination technology. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a fly ash-based defluorination adsorbent material and a preparation method thereof to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a fly ash-based defluorination adsorbent material, which comprises fly ash, a hydroxyapatite modifier and a regulating liquid, wherein the mass ratio of the fly ash, the hydroxyapatite modifier and the regulating liquid is (4-6): (2-4):9.

[0007] Preferably, the preparation method of the hydroxyapatite modifier is:

[0008] S01: Preparation of modified hydroxyapatite bodies:

[0009] S011: treating the hydroxyapatite with proton irradiation at a power of 350-400 W for a time of 20-30 min, and obtaining irradiated hydroxyapatite after the irradiation is completed;

[0010] S012: adding 2-4 parts of silane coupling agent KH560 and 1-3 parts of lanthanum chloride solution to 4-7 parts of chitosan solution, and then adding 3-5 parts of flake graphene agent and mixing well to obtain a modified solution;

[0011] S013: the irradiated hydroxyapatite and the modifying liquid are stirred and modified in a weight ratio of 2:5, and after the stirring is completed, the mixture is washed with water and dried to obtain a modified hydroxyapatite body;

[0012] S02: 4-7 parts of modified hydroxyapatite, 1-3 parts of nano-silica sol, 2-5 parts of yttrium nitrate solution with a mass fraction of 4-6% and 1-2 parts of urea are mixed and ball-milled. After the ball-milling is completed, the mixture is washed with water and dried to obtain a hydroxyapatite modifier.

[0013] Preferably, the mass fraction of the lanthanum chloride solution is 2-5%; the mass fraction of the chitosan solution is 3-6%.

[0014] Preferably, the stirring speed of the stirring modification treatment is 450-650 r / min, and the stirring time is 20-30 min; the ball milling speed of the blending ball milling treatment is 1500 r / min, and the ball milling is 2 h.

[0015] Preferably, the preparation method of the flaky graphene agent is:

[0016] 4-6 parts of flaky graphene are immersed in 10-15 parts of dopamine hydrochloride solution, and then 1-3 parts of sodium dodecylbenzene sulfonate, 2-4 parts of cobalt nitrate solution and 1-3 parts of silane coupling agent KH550 are added, mixed and stirred, and after stirring, washed with water and dried to obtain a flaky graphene agent.

[0017] Preferably, the mass fraction of the dopamine hydrochloride solution is 2-6%; the mass fraction of the cobalt nitrate solution is 3-5%.

[0018] Preferably, the stirring speed of the blending and stirring process is 450-550 r / min, and the stirring time is 30-40 min.

[0019] Preferably, the preparation method of the regulating solution is:

[0020] S101: heat-treating the aluminum oxide at 115-125° C. for 10-15 minutes, then air-cooling to room temperature, and then adding the aluminum oxide into a sufficient amount of sodium alginate solution and mixing them fully to obtain an aluminum oxide liquid;

[0021] S102: Alumina liquid, sodium silicate solution and stearic acid are mixed in a weight ratio of 3:7:1 to obtain a regulating solution.

[0022] Preferably, the mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the sodium alginate solution is 4-6%.

[0023] The present invention also provides a method for preparing a fly ash-based defluorination adsorbent material. The fly ash, hydroxyapatite modifier and regulating liquid are mixed and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours to obtain the fly ash-based defluorination adsorbent material.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The fly ash-based defluorination adsorbent material of the present invention adopts fly ash, hydroxyapatite modifier and regulating liquid to coordinate and cooperate, optimizes the activity performance of hydroxyapatite modifier through irradiation, and then adjusts and improves through the modifying liquid, the silane coupling agent KH560, lanthanum chloride solution, chitosan solution and flaky graphene agent in the modifying liquid cooperate with each other and work together, and the flaky graphene is treated with dopamine hydrochloride solution, sodium dodecylbenzene sulfonate, cobalt nitrate solution and silane coupling agent KH550 to form a fluorine-free adsorbent material based on fly ash. The blending and synergy are used to enhance the blending and preparation effect of the flaky graphene and the raw materials in the modified liquid. The alumina in the modified liquid is heat treated at 115-125°C for 10-15 minutes, then air-cooled to room temperature, and then sent into a sufficient amount of sodium alginate solution for full blending to obtain an alumina liquid, and then coordinated with the sodium silicate solution and stearic acid. Through the blending and synergy between the raw materials, the fly ash-based defluorination adsorbent prepared has excellent fluoride ion removal efficiency, high defluorination rate, and efficient and rapid defluorination. DETAILED DESCRIPTION

[0026] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] A fly ash-based defluorination adsorbent material of this embodiment comprises fly ash, a hydroxyapatite modifier and a regulating liquid, wherein the mass ratio of the fly ash, the hydroxyapatite modifier and the regulating liquid is (4-6):(2-4):9.

[0028] The preparation method of the hydroxyapatite modifier of this embodiment is:

[0029] S01: Preparation of modified hydroxyapatite bodies:

[0030] S011: treating the hydroxyapatite with proton irradiation at a power of 350-400 W for a time of 20-30 min, and obtaining irradiated hydroxyapatite after the irradiation is completed;

[0031] S012: adding 2-4 parts of silane coupling agent KH560 and 1-3 parts of lanthanum chloride solution to 4-7 parts of chitosan solution, and then adding 3-5 parts of flake graphene agent and mixing well to obtain a modified solution;

[0032] S013: the irradiated hydroxyapatite and the modifying liquid are stirred and modified in a weight ratio of 2:5, and after the stirring is completed, the mixture is washed with water and dried to obtain a modified hydroxyapatite body;

[0033] S02: 4-7 parts of modified hydroxyapatite, 1-3 parts of nano-silica sol, 2-5 parts of yttrium nitrate solution with a mass fraction of 4-6% and 1-2 parts of urea are mixed and ball-milled. After the ball-milling is completed, the mixture is washed with water and dried to obtain a hydroxyapatite modifier.

[0034] The mass fraction of the lanthanum chloride solution in this embodiment is 2-5%; the mass fraction of the chitosan solution is 3-6%.

[0035] The stirring speed of the stirring modification treatment in this embodiment is 450-650 r / min, and the stirring time is 20-30 min; the ball milling speed of the blending ball milling treatment is 1500 r / min, and the ball milling is 2 h.

[0036] The preparation method of the flake graphene agent of this embodiment is:

[0037] 4-6 parts of flaky graphene are immersed in 10-15 parts of dopamine hydrochloride solution, and then 1-3 parts of sodium dodecylbenzene sulfonate, 2-4 parts of cobalt nitrate solution and 1-3 parts of silane coupling agent KH550 are added, mixed and stirred, and after stirring, washed with water and dried to obtain a flaky graphene agent.

[0038] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2-6%; the mass fraction of the cobalt nitrate solution is 3-5%.

[0039] The stirring speed of the blending and stirring process in this embodiment is 450-550r / min, and the stirring time is 30-40min.

[0040] The preparation method of the regulating solution of this embodiment is:

[0041] S101: heat-treating the aluminum oxide at 115-125° C. for 10-15 minutes, then air-cooling to room temperature, and then adding the aluminum oxide into a sufficient amount of sodium alginate solution and mixing them fully to obtain an aluminum oxide liquid;

[0042] S102: Alumina liquid, sodium silicate solution and stearic acid are mixed in a weight ratio of 3:7:1 to obtain a regulating solution.

[0043] The mass fraction of the sodium silicate solution in this embodiment is 2-5%; the mass fraction of the sodium alginate solution is 4-6%.

[0044] In the present embodiment, a method for preparing a fly ash-based defluorination adsorbent material is provided, wherein fly ash, a hydroxyapatite modifier and a regulating liquid are mixed and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours to obtain a fly ash-based defluorination adsorbent material.

[0045] Example 1

[0046] The present embodiment provides a fly ash-based defluorination adsorbent material, which comprises fly ash, a hydroxyapatite modifier and a regulating liquid, wherein the mass ratio of the fly ash, the hydroxyapatite modifier and the regulating liquid is 4:2:9.

[0047] The preparation method of the hydroxyapatite modifier of this embodiment is:

[0048] S01: Preparation of modified hydroxyapatite bodies:

[0049] S011: treating the hydroxyapatite with proton irradiation, the irradiation power is 350W, the irradiation time is 20min, and the irradiation is completed to obtain irradiated hydroxyapatite;

[0050] S012: adding 2 parts of silane coupling agent KH560 and 1 part of lanthanum chloride solution to 4 parts of chitosan solution, and then adding 3 parts of flake graphene agent and mixing thoroughly to obtain a modified solution;

[0051] S013: the irradiated hydroxyapatite and the modifying liquid are stirred and modified in a weight ratio of 2:5, and after the stirring is completed, the mixture is washed with water and dried to obtain a modified hydroxyapatite body;

[0052] S02: 4 parts of modified hydroxyapatite, 1 part of nano-silica sol, 2 parts of 4% by mass yttrium nitrate solution and 1 part of urea are mixed and ball-milled. After the ball-milling is completed, the mixture is washed with water and dried to obtain a hydroxyapatite modifier.

[0053] The mass fraction of the lanthanum chloride solution in this embodiment is 2%; the mass fraction of the chitosan solution is 3%.

[0054] The stirring speed of the stirring modification treatment in this embodiment is 450 r / min, and the stirring time is 20 min; the ball milling speed of the blending ball milling treatment is 1500 r / min, and the ball milling is 2 h.

[0055] The preparation method of the flake graphene agent of this embodiment is:

[0056] Four parts of flaky graphene were immersed in 10 parts of dopamine hydrochloride solution, and then 1 part of sodium dodecylbenzene sulfonate, 2 parts of cobalt nitrate solution and 1 part of silane coupling agent KH550 were added, mixed and stirred, and after stirring, washed with water and dried to obtain a flaky graphene agent.

[0057] The mass fraction of the dopamine hydrochloride solution in this embodiment is 2%; the mass fraction of the cobalt nitrate solution is 3%.

[0058] The stirring speed of the blending and stirring process in this embodiment is 450r / min, and the stirring time is 30min.

[0059] The preparation method of the regulating solution of this embodiment is:

[0060] S101: heat-treating the aluminum oxide at 115° C. for 10 min, then air-cooling to room temperature, and then adding the aluminum oxide into a sufficient amount of sodium alginate solution and mixing them fully to obtain an aluminum oxide liquid;

[0061] S102: Alumina liquid, sodium silicate solution and stearic acid are mixed in a weight ratio of 3:7:1 to obtain a regulating solution.

[0062] The mass fraction of the sodium silicate solution in this embodiment is 2%; the mass fraction of the sodium alginate solution is 4%.

[0063] In the present embodiment, a method for preparing a fly ash-based defluorination adsorbent material is provided, wherein fly ash, a hydroxyapatite modifier and a regulating liquid are mixed and ball-milled at a ball-milling speed of 1000 r / min for 2 hours to obtain a fly ash-based defluorination adsorbent material.

[0064] Example 2

[0065] The present embodiment provides a fly ash-based defluorination adsorbent material, which comprises fly ash, a hydroxyapatite modifier and a regulating liquid, wherein the mass ratio of the fly ash, the hydroxyapatite modifier and the regulating liquid is 6:4:9.

[0066] The preparation method of the hydroxyapatite modifier of this embodiment is:

[0067] S01: Preparation of modified hydroxyapatite bodies:

[0068] S011: treating the hydroxyapatite with proton irradiation, the irradiation power is 400 W, the irradiation time is 30 min, and the irradiation is completed to obtain irradiated hydroxyapatite;

[0069] S012: adding 4 parts of silane coupling agent KH560 and 3 parts of lanthanum chloride solution to 7 parts of chitosan solution, and then adding 5 parts of flake graphene agent and blending thoroughly to obtain a modified solution;

[0070] S013: the irradiated hydroxyapatite and the modifying liquid are stirred and modified in a weight ratio of 2:5, and after the stirring is completed, the mixture is washed with water and dried to obtain a modified hydroxyapatite body;

[0071] S02: 7 parts of modified hydroxyapatite, 3 parts of nano-silica sol, 5 parts of 6% by mass yttrium nitrate solution and 2 parts of urea are mixed and ball-milled. After the ball-milling is completed, the mixture is washed with water and dried to obtain a hydroxyapatite modifier.

[0072] The mass fraction of the lanthanum chloride solution in this embodiment is 5%; the mass fraction of the chitosan solution is 6%.

[0073] The stirring speed of the stirring modification treatment in this embodiment is 650 r / min, and the stirring time is 30 min; the ball milling speed of the blending ball milling treatment is 1500 r / min, and the ball milling is 2 h.

[0074] The preparation method of the flake graphene agent of this embodiment is:

[0075] 6 parts of flaky graphene were immersed in 15 parts of dopamine hydrochloride solution, and then 3 parts of sodium dodecylbenzene sulfonate, 4 parts of cobalt nitrate solution and 3 parts of silane coupling agent KH550 were added, mixed and stirred, and after stirring, washed with water and dried to obtain a flaky graphene agent.

[0076] The mass fraction of the dopamine hydrochloride solution in this embodiment is 6%; the mass fraction of the cobalt nitrate solution is 5%.

[0077] The stirring speed of the blending and stirring process in this embodiment is 550r / min, and the stirring time is 40min.

[0078] The preparation method of the regulating solution of this embodiment is:

[0079] S101: heat-treating the aluminum oxide at 125° C. for 15 min, then air-cooling to room temperature, and then adding the aluminum oxide into a sufficient amount of sodium alginate solution and mixing them fully to obtain an aluminum oxide liquid;

[0080] S102: Alumina liquid, sodium silicate solution and stearic acid are mixed in a weight ratio of 3:7:1 to obtain a regulating solution.

[0081] The mass fraction of the sodium silicate solution in this embodiment is 5%; the mass fraction of the sodium alginate solution is 6%.

[0082] In the present embodiment, a method for preparing a fly ash-based defluorination adsorbent material is provided, wherein fly ash, a hydroxyapatite modifier and a regulating liquid are mixed and ball-milled at a ball-milling speed of 1500 r / min for 2 hours to obtain a fly ash-based defluorination adsorbent material.

[0083] Example 3

[0084] The present embodiment provides a fly ash-based defluorination adsorbent material, which comprises fly ash, a hydroxyapatite modifier and a regulating liquid, wherein the mass ratio of the fly ash, the hydroxyapatite modifier and the regulating liquid is 5:3:9.

[0085] The preparation method of the hydroxyapatite modifier of this embodiment is:

[0086] S01: Preparation of modified hydroxyapatite bodies:

[0087] S011: treating the hydroxyapatite with proton irradiation, the irradiation power is 370W, the irradiation time is 25min, and the irradiation is completed to obtain irradiated hydroxyapatite;

[0088] S012: adding 3 parts of silane coupling agent KH560 and 2 parts of lanthanum chloride solution to 5.5 parts of chitosan solution, and then adding 4 parts of flake graphene agent and mixing thoroughly to obtain a modified solution;

[0089] S013: the irradiated hydroxyapatite and the modifying liquid are stirred and modified in a weight ratio of 2:5, and after the stirring is completed, the mixture is washed with water and dried to obtain a modified hydroxyapatite body;

[0090] S02: 5.5 parts of modified hydroxyapatite, 2 parts of nano-silica sol, 3.5 parts of 5% by mass yttrium nitrate solution and 1.5 parts of urea are mixed and ball-milled. After the ball-milling is completed, the mixture is washed with water and dried to obtain a hydroxyapatite modifier.

[0091] The mass fraction of the lanthanum chloride solution in this embodiment is 3.5%; the mass fraction of the chitosan solution is 4.5%.

[0092] The stirring speed of the stirring modification treatment in this embodiment is 500 r / min, and the stirring time is 25 min; the ball milling speed of the blending ball milling treatment is 1500 r / min, and the ball milling is 2 h.

[0093] The preparation method of the flake graphene agent of this embodiment is:

[0094] 5 parts of flaky graphene were immersed in 12.5 parts of dopamine hydrochloride solution, and then 2 parts of sodium dodecylbenzene sulfonate, 3 parts of cobalt nitrate solution and 2 parts of silane coupling agent KH550 were added, mixed and stirred, and after stirring, washed with water and dried to obtain a flaky graphene agent.

[0095] The mass fraction of the dopamine hydrochloride solution in this embodiment is 4%; the mass fraction of the cobalt nitrate solution is 4%.

[0096] The stirring speed of the blending and stirring process in this embodiment is 500 r / min, and the stirring time is 35 min.

[0097] The preparation method of the regulating solution of this embodiment is:

[0098] S101: heat-treating the aluminum oxide at 120° C. for 12.5 min, then air-cooling to room temperature, and then adding the aluminum oxide into a sufficient amount of sodium alginate solution and mixing them fully to obtain an aluminum oxide liquid;

[0099] S102: Alumina liquid, sodium silicate solution and stearic acid are mixed in a weight ratio of 3:7:1 to obtain a regulating solution.

[0100] The mass fraction of the sodium silicate solution in this embodiment is 3.5%; the mass fraction of the sodium alginate solution is 5%.

[0101] In the present embodiment, a method for preparing a fly ash-based defluorination adsorbent material is provided, wherein fly ash, a hydroxyapatite modifier and a regulating liquid are mixed and ball-milled at a ball-milling speed of 1250 r / min for 2 hours to obtain a fly ash-based defluorination adsorbent material.

[0102] Example 4

[0103] The present embodiment provides a fly ash-based defluorination adsorbent material, which comprises fly ash, a hydroxyapatite modifier and a regulating liquid, wherein the mass ratio of the fly ash, the hydroxyapatite modifier and the regulating liquid is 5:3:9.

[0104] The preparation method of the hydroxyapatite modifier of this embodiment is:

[0105] S01: Preparation of modified hydroxyapatite bodies:

[0106] S011: treating the hydroxyapatite with proton irradiation, with an irradiation power of 360 W and an irradiation time of 22 min. After the irradiation is completed, irradiated hydroxyapatite is obtained;

[0107] S012: adding 3 parts of silane coupling agent KH560 and 2 parts of lanthanum chloride solution to 5 parts of chitosan solution, and then adding 4 parts of flake graphene agent and mixing thoroughly to obtain a modified solution;

[0108] S013: the irradiated hydroxyapatite and the modifying liquid are stirred and modified in a weight ratio of 2:5, and after the stirring is completed, the mixture is washed with water and dried to obtain a modified hydroxyapatite body;

[0109] S02: 5 parts of modified hydroxyapatite, 2 parts of nano-silica sol, 3 parts of 5% by mass yttrium nitrate solution and 1.2 parts of urea are mixed and ball-milled. After the ball-milling is completed, the mixture is washed with water and dried to obtain a hydroxyapatite modifier.

[0110] The mass fraction of the lanthanum chloride solution in this embodiment is 3%; the mass fraction of the chitosan solution is 4%.

[0111] The stirring speed of the stirring modification treatment in this embodiment is 500 r / min, and the stirring time is 22 min; the ball milling speed of the blending ball milling treatment is 1500 r / min, and the ball milling is 2 h.

[0112] The preparation method of the flake graphene agent of this embodiment is:

[0113] Immerse 5 parts of flaky graphene in 12 parts of dopamine hydrochloride solution, then add 2 parts of sodium dodecylbenzene sulfonate, 3 parts of cobalt nitrate solution and 2 parts of silane coupling agent KH550, mix and stir, and after stirring, wash with water and dry to obtain a flaky graphene agent.

[0114] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3%; the mass fraction of the cobalt nitrate solution is 4%.

[0115] The stirring speed of the blending and stirring process in this embodiment is 510 r / min, and the stirring time is 32 min.

[0116] The preparation method of the regulating solution of this embodiment is:

[0117] S101: heat-treating the aluminum oxide at 117° C. for 12 minutes, then air-cooling to room temperature, and then adding the aluminum oxide into a sufficient amount of sodium alginate solution and mixing them fully to obtain an aluminum oxide liquid;

[0118] S102: Alumina liquid, sodium silicate solution and stearic acid are mixed in a weight ratio of 3:7:1 to obtain a regulating solution.

[0119] The mass fraction of the sodium silicate solution in this embodiment is 3%; the mass fraction of the sodium alginate solution is 5%.

[0120] In the preparation method of a fly ash-based defluorination adsorbent material of the present embodiment, fly ash, hydroxyapatite modifier and regulating liquid are mixed and ball-milled at a ball-milling speed of 1220 r / min for 2 hours to obtain a fly ash-based defluorination adsorbent material.

[0121] Comparative Example 1

[0122] The difference from Example 3 is that no hydroxyapatite modifier is added.

[0123] Comparative Example 2

[0124] The difference from Example 3 is that no modifying liquid treatment is used in the preparation of the hydroxyapatite modifier.

[0125] Comparative Example 3

[0126] The difference from Example 3 is that no flake graphene agent is added to the modified liquid.

[0127] Comparative Example 4

[0128] The difference from Example 3 is that the flaky graphene agent is replaced by flaky graphene.

[0129] Comparative Example 5

[0130] The difference from Example 3 is that S02 treatment is not adopted.

[0131] Comparative Example 6

[0132] The difference from Example 3 is that no conditioning liquid was added.

[0133] Comparative Example 7

[0134] The difference from Example 3 is that no alumina liquid is added to the regulating liquid.

[0135] The performance test results of the products of Examples 1-4 and Comparative Examples 1-7 of the present invention are as follows.

[0136]

[0137] It can be seen from Examples 1-4 and Comparative Examples 1-7 that the products of Examples 1-4 of the present invention have excellent fluorine removal rates, and the products can remove fluorine quickly and have excellent fluorine removal effects;

[0138] When neither hydroxyapatite modifier nor regulating liquid is added to the product, the fluorine removal efficiency of the product has a significant trend of deterioration. When the two are used in combination, the performance of the product is most significant.

[0139] In the preparation of the hydroxyapatite modifier, no modifying liquid treatment was used, no flaky graphene agent was added to the modifying liquid, the flaky graphene agent was replaced by flaky graphene, SO2 treatment was not used, and no alumina liquid was added to the regulating liquid. The performance of the product showed a trend of deterioration. Only the hydroxyapatite modifier obtained by the method of the present invention had the most significant performance effect of the product. The effects of other methods were not as obvious as those of the present invention.

[0140] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0141] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A fly ash-based defluorination adsorbent material, characterized in that: The adsorbent material includes fly ash, hydroxyapatite modifier and regulating liquid, wherein the mass ratio of fly ash, hydroxyapatite modifier and regulating liquid is (4-6): (2-4): 9; The preparation method of the hydroxyapatite modifier is: S01: Preparation of modified hydroxyapatite bodies: S011: treating the hydroxyapatite with proton irradiation at a power of 350-400 W for a time of 20-30 min, and obtaining irradiated hydroxyapatite after the irradiation is completed; S012: adding 2-4 parts of silane coupling agent KH560 and 1-3 parts of lanthanum chloride solution to 4-7 parts of chitosan solution, and then adding 3-5 parts of flake graphene agent and mixing well to obtain a modified solution; S013: the irradiated hydroxyapatite and the modifying liquid are stirred and modified in a weight ratio of 2:5, and after the stirring is completed, the mixture is washed with water and dried to obtain a modified hydroxyapatite body; S02: 4-7 parts of modified hydroxyapatite, 1-3 parts of nano-silica sol, 2-5 parts of yttrium nitrate solution with a mass fraction of 4-6% and 1-2 parts of urea are mixed and ball-milled, and after the ball-milling is completed, the mixture is washed with water and dried to obtain a hydroxyapatite modifier; The preparation method of the regulating solution is: S101: heat-treating the aluminum oxide at 115-125° C. for 10-15 minutes, then air-cooling to room temperature, and then adding the aluminum oxide into a sufficient amount of sodium alginate solution and mixing them fully to obtain an aluminum oxide liquid; S102: mixing aluminum oxide solution, sodium silicate solution and stearic acid in a weight ratio of 3:7:1 to obtain a regulating solution; The preparation method of the flaky graphene agent is: Immerse 4-6 parts of flaky graphene in 10-15 parts of dopamine hydrochloride solution, then add 1-3 parts of sodium dodecylbenzene sulfonate, 2-4 parts of cobalt nitrate solution and 1-3 parts of silane coupling agent KH550, mix and stir, wash with water and dry after stirring to obtain a flaky graphene agent; The preparation method of the fly ash-based defluorination adsorbent material is as follows: fly ash, hydroxyapatite modifier and regulating liquid are mixed and ball-milled at a ball-milling speed of 1000-1500r / min for 2h, and the fly ash-based defluorination adsorbent material is obtained after the ball-milling is completed.

2. A fly ash-based defluorination adsorbent material according to claim 1, characterized in that: The mass fraction of the lanthanum chloride solution is 2-5%; the mass fraction of the chitosan solution is 3-6%.

3. The fly ash-based defluorination adsorbent material according to claim 1, characterized in that: The stirring speed of the stirring modification treatment is 450-650 r / min, and the stirring time is 20-30 min; the ball milling speed of the blending ball milling treatment is 1500 r / min, and the ball milling is 2 h.

4. The fly ash-based defluorination adsorbent material according to claim 1, characterized in that: The mass fraction of the dopamine hydrochloride solution is 2-6%; the mass fraction of the cobalt nitrate solution is 3-5%.

5. The fly ash-based defluorination adsorbent material according to claim 1, characterized in that: The mixing speed of the blending and stirring process is 450-550 r / min, and the mixing time is 30-40 min.

6. The fly ash-based defluorination adsorbent material according to claim 1, characterized in that: The mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the sodium alginate solution is 4-6%.

Citation Information

Cited By

  • High-selectivity PFAS pollutant treatment environment-friendly adsorption material based on solid waste derivation and preparation method of high-selectivity PFAS pollutant treatment environment-friendly adsorption material

    CN120644169A